CONTRIBUTING TO ENTREPRENEURSHIP DEVELOPMENT AT KESATUAN HIGH SCHOOL BOGOR: WORKSHOP ON BRANDING STRATEGY - Zubaedah, Siti Yasmina; Caroline, Laura (Jurnal Pengabdian dan Kewirausahaan, 2025)
Community service provides various opportunities for academicians to disseminate knowledge and contribute to the development of society. In August 2024, the UBM Management Program contributed to community service at Kesatuan High School in Bogor, West Java, in a workshop on branding strategy. The growing attention towards developing entrepreneurial capabilities at a young age has motivated educators to incorporate entrepreneurship development programs in schools. Kesatuan High School is one of the high schools that included a creative entrepreneur development program in its 10th-grade curriculum. The community service in this article adopts several research methods, including a literature review and a combined qualitative-quantitative analysis. The lecturer began the workshop by explaining Schumpeter’s entrepreneurship theory as the foundational concept of the role of entrepreneurs. Creative entrepreneurs are essential to be able to solve management problems, combine resources and processes in different manners to build competitive advantage. Summarizing from various sources, students learned that products refer to tangible attributes, while brands refer to the intangible attributes offered by the business. Based on the descriptive analyses, the feedback survey found that the overall score for the workshop was 3.075 out of 4.00, which demonstrated positive feedback from workshop participants. Regardless of the slight variances between the feedback components, the scores indicate that the workshop was delivered optimally and in line with the predetermined objectives. Hence, this community service exemplifies an alternative model for faculty members to share knowledge and contribute to improving the learning experience as well as advancing high school education